Hubungan Antara Status Gizi dan Lingkar Pinggang pada Civitas Akademika di Universitas Yarsi dan Tinjauannya Menurut Pandangan Islam - Jiwandani, Rizka Zahra; Wuryanti, Sri; Arifandi, Firman; Asiah, Nur (Green Publisher Indonesia, 2025)
Nutritional status is an important health indicator that can be assessed through Body Mass Index (BMI), however this parameter has limitations in describing visceral fat distribution associated with metabolic disease risk. Waist circumference is a more sensitive indicator for identifying central obesity. This study aims to determine the description of nutritional status, waist circumference, and the relationship between nutritional status and waist circumference among the academic community at YARSI University and its review according to Islamic perspective. This study is a quantitative analytic research with cross-sectional design involving 74 respondents aged 20-60 years. Primary data were obtained through direct measurements using stature meter, body weight scale, and measuring tape. Data analysis used univariate analysis and bivariate analysis with Spearman correlation test. The results showed that 75.6% of respondents had excess nutritional status with obesity II (45.9%) and obesity I (29.7%), exceeding the national prevalence of 21.8%. The majority of respondents had excess waist circumference, namely 51.4% women (>80 cm) and 29.7% men (>90 cm). The relationship between BMI and waist circumference overall was not significant (r = 0.172; p = 0.144), but showed a moderate and significant positive relationship in the analysis based on gender, namely men (r = 0.544; p = 0.005) and women (r = 0.569; p = 0.000). This study concludes that BMI cannot be used alone in assessing body fat distribution, therefore waist circumference measurement needs to be used as an additional indicator to detect central obesity risk. From an Islamic perspective, maintaining nutritional balance is an implementation of the principles of halalan tayyiban and the prohibition of isrāf as commanded in the Qur'an.